Multi-energy-system design and experimental research of natural-energy-driven unmanned surface vehicle. (15th November 2021) - Li, Ye; Zhang, Weixin; Liao, Yulei; Jia, Qi; Jiang, Quanquan
Abstract: Natural-energy-driven surface vehicle, which is abbreviated to NSV, is a new type of marine vehicle driven by marine natural energy. In this paper, a NSV, which absorbs wave, wind and solar energy as power input, is designed and developed. Firstly, the hull form of NSV is designed. Secondly, the multi-body dynamic model (MBD) of NSV is established. Thirdly, a method which simulates multi-body motion of NSV in ocean waves is raised by combining MBD and CFD, by which the optimum position of hydrofoil is determined and the effect of encounter angle between wave and NSV on thrust of hydrofoil is studied. Then the wind turbine is added to MBD to calculate the power of wind turbine and total resistance of NSV from flat water to the 4th sea state, by which the energy consumption of NSV is calculated and the area of solar panel is determined. It's found that the energy consumption is the largest when NSV sails in flat water compared with other sea states. Finally, NSV prototype is manufactured and ocean experiment is carried out. Through the ocean experiment, it is concluded that NSV's absorption of natural energy supplements its energy consumption. Highlights: An unmanned surface vehicle driven by wind, solar and wave energy is designed and developed. The multi-body dynamic model (MBD) of NSV is established. A method simulating multi-body motion of NSV in ocean waves is raised by combining MBD and CFD. It's found the energy consumption is the largest when NSV sails in flat water.